ЭПИДЕМИОЛОГИЯ ДЕТСКОГО ОЖИРЕНИЯ В МИРЕ (International Journal of Scientific Pediatrics, 2024)
Today, one of the pressing issues for modern society is the fight against risk factors for the development of non-communicable diseases, including obesity. This article provides current data on the epidemiology of obesity in children and adolescents in the world. Obesity is recognized as a global problem as there is an increase in obesity worldwide. Some researchers estimate that by 2030, nearly a third of the world's population could be overweight or obese. This problem occurs not only in developed countries, but also in low- and middle-income countries. According to the WHO, between 1975 and 2016, worldwide, the proportion of children and adolescents aged 5–19 years who are overweight or obese more than quadrupled, from 4% to 18% (WHO, 2020). In 2019, approximately 38 million children under 5 years of age were overweight or obese (WHO, 2020). Childhood obesity has a 70-80% likelihood of leading to adolescent and adult obesity. Today, obesity is considered the most important risk factor for cardiovascular diseases (CVD) and metabolic disorders (according to WHO, it determines the development of up to 44-57% of type 2 diabetes mellitus, 30% of cholelithiasis, 17-23% of cases of coronary heart disease, 17% - arterial hypertension, 14% - osteoarthritis) and reproductive dysfunction and an increased risk of developing cancer.
Keywords: obesity; epidemiology; metabolic disorders